METODOLOGIA INVESTIGATIVA NO ENSINO DA CINÉTICA QUÍMICA (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
Chemical processes present in the transformation industries, the aging of our organism, the growth of plants and the generation of rains are examples of processes controlled by kinetic factors that permeates our daily routine. However, classes based on abstract example and by excessive mathematical calculations decrease the students’ interest in learning about this content, as well as, do not contribute to train teachers to be aware of the importance of chemical science and its relation to society and the environment. In order to make a pedagogical intervention in the teaching of chemical kinetics, this work aimed to evaluating if an investigative methodology to provide for the student the ability to investigate and reflect on facts observed in the discipline of chemical kinetics. The research developed with students of the Licentiate in Chemistry of a Public Institution, showed that the investigate methodology was able to develop the students’ ability to observe and reflect on the occurrence of a chemical reaction. However, the absence of mathematical concepts, including that of derivative, made it difficult for students to develop an experimental procedure, requiring the planning of actions in the laboratory. It was verified that the investigative methodology favors the interaction and communication between the pairs, helping in the establishment of an experimental methodology to be applied by each group to answer the questions regarding the reaction of thiosulphate in acid environment. This practice brought to the educational environmental the discussion about the generation of laboratory residue, qualifying the students to work with enough quantities of reagents to achieve the same results that would be reached with large quantities, besides associating the pedagogical intervention to the influences of the chemical kinetics on the environmental issues.
Keywords: Teacher Training; Investigative Methodology; Chemical-Kinetic; Thiosulphate